Influencia de los padres de familia en el rendimiento escolar de los alumnos del tercer año de educación básica.Estudio del caso de la escuela dr. Alfredo Monge de la comunidad de Cialpa Viejo, cantón Colta, provincia del Chimborazo. - Toctaguano Inca, Carmen Floriza (2014)
The yield of the students depends since in its bigger part of the family parents they play an important paper in the education of its children. In the measure in that these, assume the list that corresponds them, the yield it improves ostensibly in the children, but when this situation is not given, the most probable thing is that the yield of the students in the school shrinks and finally it is translated in indexes of school reprehension. In the carried out investigation it was sought to go to the source and to check the existent relationship between yield and family parents' support and in what measure the parents of family of this community and particularly those that have children in this educational center have fulfilled this list; with the result that to sustain it, a brief bibliographical revision was made on the topic, then by means of a survey, information was picked up about the influence degree that they have the family parents in the school yield of its children.